1995
DOI: 10.1091/mbc.6.12.1707
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of distinct types of gap junction channels by similar phosphorylating conditions.

Abstract: Under control conditions, the distinct types of gap junction channels could be distinguished on the basis of their permeability and single channel properties. Under various phosphorylating conditions, these channels behaved differently. Whereas agonists/antagonist of PKA did not affect permeability and conductance of all gap junction channels, variable changes were observed under PKC stimulation. Cx45 channels exhibited an additional conductance state, the detection of the smaller conductance states of Cx43 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(108 citation statements)
references
References 54 publications
6
99
1
2
Order By: Relevance
“…Phosphorylation could have a direct effect on channel properties of Cx35/36 gap junctions, as has been seen for a number of other connexin channels. For example, Cx43 channels expressed in SkHep1 cells show a reversible shift from a 90-100 pS main state to a 60-70 pS subconductance state with activation of PKC (Moreno et al, 1994;Kwak et al, 1995). These effects are mediated by phosphorylation of Ser368 by PKC (Lampe et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation could have a direct effect on channel properties of Cx35/36 gap junctions, as has been seen for a number of other connexin channels. For example, Cx43 channels expressed in SkHep1 cells show a reversible shift from a 90-100 pS main state to a 60-70 pS subconductance state with activation of PKC (Moreno et al, 1994;Kwak et al, 1995). These effects are mediated by phosphorylation of Ser368 by PKC (Lampe et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The single channel conductance is about 200 pS, 80 pS and 20 pS, for Cx40, Cx43 and Cx45 channel, respectively [42,62,63]. The conductance values can be influenced by many factors such as intracellular calcium, magnesium, sodium ion concentration, pH, hypoxia and the phosphorylation state of connexins [34,36].…”
Section: The Distribution Of Gap Junctionsmentioning
confidence: 99%
“…Various phospho-forms of Cx43 can be resolved by immunoblotting, making it a useful technique to evaluate its state of phosphorylation (13)(14)(15)20,25,29,30,33,35,37,41,42,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). Nonetheless, not all changes in the state of phosphorylation of Cx43 alter the electrophoretic mobility of the protein (42).…”
Section: Phosphorylation Of Cxs and Possible Functional Rolesmentioning
confidence: 99%
“…gag-fps and ras oncogen) alter intercellular gap junctional communication and effect of some these agents depends on cell and Cx type (13,16,20,30,(34)(35)(36)38,(41)(42)(43)(44)(45)(46)(47). It has also been suggested that phosphorylation of Cx43 in seryl residues might be involved in a number of different processes including its insertion into the plasma membrane (56), increase in its degradation, changes in unitary conductance of single gap junction channels and closure of gap junction channels (13,16,45,57,61,62).…”
Section: Phosphorylation Of Cxs and Possible Functional Rolesmentioning
confidence: 99%
See 1 more Smart Citation